Green Biopolymers and their Nanocomposites - Gnanasekaran, Dhorali; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises a collection of chapters on green biopolymer nanocomposites. The book discusses the preparation, properties, and applications of different types of biodegradable polymers. An overview of recent advances in the fabrication of biopolymers nanocomposites from a variety of sources, including organic and inorganic nanomaterials, is presented. The book highlights the importance and impact of eco-friendly green nanocomposites, both environmentally and economically. The contents of this book will prove useful for students, researchers, and professionals working in the field of nanocomposites and green technology. .
1. Green biopolymers and their Nanocomposites -- 2. Green polymer composites, based on polylactic acid (PLA) and fibers -- 3. Magnetic Cellulose Green Nano-Composite Adsorbents for the Removal of Heavy Metal Ions in Water/Waste Water -- 4. Biocomposites reinforced with nanocellulose for packaging applications -- 5. Chitosan in food packaging applications -- 6. Nanostructured Biopolymer Composites for Orthopedic Application -- 7. Natural Biopolymers for Drug Delivery -- 8. Opportunities for PLA and its bio-blends for various applications -- 9. Biodegradable polymer based nanocomposite -- 10. The use of Biopolymers in Food Packaging -- 11. Biopolymer Composites and Bionanocomposites for Energy Applications -- 12. Biopolymers and Nanocomposites for Civil Engineering Applications -- 13. Bioactivity of Plant Extracts Encapsulated in Polymeric Nanofibres for Medicine and Drug Delivery -- 14. Eco-friendly Polymer Nanocomposites and itsApplications -- 15. Polysaccharide Nanocomposites.
Keywords: Biomaterials; Green chemistry; Nanotechnology; Environmental chemistry; Biomaterials; Green Chemistry; Nanotechnology; Environmental Chemistry